Synthesis of publicist history: reflective stages of the German public communication science - da Silva Gomes, Fábio (2019)
The book analyzes the evolution of the studies of German communication in line with the historical facts of the country in the twentieth century. From doctrinal objectives, going through the authoritarian pretensions of the Nazi regime, to the regulation role of thecommunication study - the book describes the evolution of scholar contributions in view of the behavioral and political changes that ruled the period portrayed. The review also describes the distinctive North American empirical influence in the various theoretical approaches thatform German journalism in human history, expounded by the book.